NATURAL SEABED GAS SEEPS AS SOURCES OF ATMOSPHERIC METHANE - Judd A.G. (My University, 2004)
Microbial and thermogenic methane migrates towards the seabed where some is utilised during microbially-mediated anaerobic oxidation. Excess methane escapes as gas seeps, which occur in a variety of geological contexts in every sea and ocean, from inter-tidal zones to deep ocean trenches. Some seeps are localised, gentle emanations; others are vigorous covering areas of >1km2; the most prolific seeps reported (offshore Georgia) produce ~40t CH4 per year. Gas bubbles lose methane to the water as they rise, so deep water seeps are unlikely to contribute to the atmosphere. However, bubbles break the surface above some shallow water seeps. Estimates of the total methane contribution to the atmosphere are poorly constrained, largely because the data set is so small. 20 Tgyr–1 is considered a realistic first approximation. This is a significant contribution to the global budget, particularly as methane from seeps is 14C-depleted. A seep measurement programme is urgently required.
Keywords: Methane; Gas seeps; Atmosphere